(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Diarrhoea remains the second leading cause of mortality in children, with an estimated 205 children under the age of 5 dying daily in Nigeria. Combination therapy of ORS with zinc tablets is the cornerstone for its management. Secondary healthcare facilities (SHFs) represent the second level of contact for patients requiring professional care; hence an appropriate prescription for diarrhoea is crucial for the survival of under-fives. Objectives To evaluate the prescription of medicines in the management of acute watery diarrhoea (AWD) in under-fives at SHFs, and determine the appropriateness of the prescriptions. Method A descriptive cross-sectional study was done at four randomly selected SHFs in Lagos State. A retrospective review of prescriptions for diarrhoea cases totaling 480, was done using records from the General Out-Patient Department from September 2018 to August 2019. A descriptive analysis was performed. Results: All cases reviewed were diagnosed as AWD occurring either alone (352; 73.3%) or in combination with malaria/fever (55; 11.5%), cough/URTI (23; 4.8%), and other conditions (50; 10.4%). Of the 352 AWD only cases, there were 121 (34.4%) prescriptions for ORS/Zinc as combined therapy without addition of antibiotics, 120 (34.1%) for antibiotics, and 134 (38.1%) for probiotics. Other prescriptions include analgesics (18.2%), injectables (9.7%) and antimalarials (8.8%). Conclusion: The study revealed suboptimal prescriptions of ORS/Zinc with the appropriateness of prescription at 34.4%. The prescription of antibiotics and other medicines which have no rehydration benefits was high.